Mathematics Literacy based on Visual-Spatial Intelligence 7th Grade Students on Discovery Learning with Performance Assessment - Khoir, Nisaul Lathifatul; Masrukan, Masrukan; Wiyanto, Wiyanto (Unnes Journal of Mathematics Education Research, 2019)
This study aims to determine the effectiveness of discovery learning with a performance assessment of students 'mathematical literacy and analyze students' mathematical literacy based on visual-spatial intelligence. This study used a mixed method with concurrent embedded. Subjects of this studi were 7th grade students of SMP An Nur Ungaran 2017/2018 school year. The results of the study show that discovery learning with performance assessment effective of students' mathematical literacy. Students with high visual-spatial intelligence can reach each indicator well, although some indicators have insignificant errors. Students with middle visual-spatial intelligence have significant errors on each indicator. Students with low visual-spatial intelligence cannot achieve every indicator of mathematical literacy. Found uniqueness in students with high visual-spatial intelligence, namely with the presence of images contained in the problem, students are helped to understand the problem presented. Understanding or communication is the main key for students to continue the next stage of mathematical literacy. However, students with high visual-spatial intelligence are constrained in algebraic material.